Efficacy and safety of acidified enteral formulae in tube fed patients in an intensive care unit - Kruger, Jeanne-Marie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Human Nutrition))--University of Stellenbosch, 2006.